OVERBURDEN VOLUME CALCULATION USING CUT AND FILL METHOD AT RHML JOBSITE (RIUNG HARAPAN MITRA LESTARI) PT. RIUNG MITRA LESTARI, TAPIN REGENCY, SOUTH KALIMANTAN PROVINCE - Bagas Firman Maulana; Moch. Abdul Kholiq (Journal of Marine-Earth Science and Technology, 2024)
Overburden is all layers of soil/rock that are above and directly cover the layer of valuable mining materials so that they need to be removed first before being able to dig up the valuable mining materials. In the process of removing overburden, its volume needs to be calculated. One method that is often used is the cut and fill calculation method. The cut and fill calculation method can be done using several software, including Surpac and Civil 3D. This study discusses the calculation of overburden volume based on data obtained from detailed topographic measurements of the situation at PT. Riung Mitra Lestari jobsite RHML located in Tapin Regency, South Kalimantan. This data consists of situation coordinate data from July 29 - August 21, 2024. The purpose of this report is to calculate overburden using Surpac and Civil 3D software. From the calculations, the overburden volume was obtained as much as 309,569 BCM in Surpac software and 310,548 BCM in Civil 3D software.